Progress for a small planet - Ward, Barbara (New York : Norton, 1979)
Progress for a Small Planet consists argues that industrialisation patterns could be made considerably less energy-intensive, less resource-consuming and less environment disruptive. The four chapters on energy are packed with data based on earlier research done by the IIED and emphasise the potential for energy conservation at an economic cost much less than the construction of nuclear plants, not speaking of the risks involved in the Faustian bargain.
Includes bibliographical references and index.
lje 17/04/2018
Loans
Keywords: Economic development; International economic relations; Conservation of natural resources; Environmental policy; Human ecology